Eek discovers Earth - Hoena, B. A.; Harpster, Steve (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2014)
When Eek discovers Earth, the boys set out to conquer it--but end up with a pile of dirty laundry instead.
When Eek discovers Earth, the boys set out to conquer it -- but end up with a pile of dirty laundry instead.
005-007.
GRL: K.
105142
Keywords: Extraterrestrial beings -- Juvenile fiction; Human-alien encounters -- Juvenile fiction; Brothers -- Juvenile fiction; Science fiction; Fiction; Juvenile works; Children's fiction